Food as a Tool of Grotesque in Contemporary Lithuanian and Latvian Fiction - Laurušaitė, Laura (Colloquia, 2025)
The article explores the interplay between grotesque and gastropoetics in contemporary Lithuanian and Latvian literature, focusing on Latvian author Guntis Berelis’s short story “Es nekad nerunāju muļķības” (“I Have Never Talked Nonsense,” 2017) and Lithuanian author Ieva Dumbrytė’s novel Šaltienos bistro (Aspic Bistro, 2021). In both texts, grotesque imagery involving food, cannibalism, and bodily transformations plays a significant narrative role and encodes social and political critique. An identified subgenre of the grotesque—gastronomic grotesque (gastrogrotesque)—emerges as a previously unexplored niche of grotesque expression in the Baltic region. Drawing on Bakhtin’s metaphor of grotesque as transformation, it is argued that the symbolism of pig and meat in these texts embodies the extreme dehumanization of individuals, either in labor (Dumbrytė) or within political systems (Berelis). The grotesque serves its conventional function of overturning traditional literary aesthetic norms while also offering a shocking perspective on contemporary issues.
Keywords: Lithuanian and Latvian contemporary literature; grotesque; food symbolism; cannibalism; social critique; aesthetics of ugliness